THE TREATMENT OF SPECIFIC AND GENERALISED SOCIAL PHOBIA IN EUROPE: A META-ANALYTIC REVIEW - Sánchez Meca, Julio; Rosa Alcázar, Ana Isabel; Olivares Rodríguez, José (Anales de Psicología / Annals of Psychology, 2004)
In this paper the results of a meta-analysis about the effectiveness of behavioural treatment on specific and generalised social phobia are presented. Fifteen European papers were included that met the selection criteria, offering a total of 35 independent studies, on which it was calculated the standardised mean difference between the pretest- postest and pretest - follow-up. The mean effect size at the postest on social phobia measures was higher for the generalised social phobia (d+ = 1.109) than for the specific subtype (d+ = 0.634). At the follow-up, the mean effect size increased in both subtypes of social phobia (d+ = 1.604 and d+ = 0.966, respectively). The differential efficacy of the different behavioural interventions are analysed and a tentative explanatory model of the effectiveness is presented for the two subtypes of social phobia. Finally, the practical and clinical implications of the results are discussed, as well as for future research.